Peran Kepala Sekolah dalam Meningkatkan Manajemen Mutu Pendidikan di SMA 4 Pab Sampali, Kecamatan Percut Sei Tuan, Kabupaten Deli Serdang, Medan - Neliwati; Putri, Adinda Julia; Evy Juliani Siregar; Salsabila Hsb, Maisa Muti (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This research aims to find out and describe the role of the principal in improving education quality management at SMA 4 PAB Sampali. The research method used in this research is descriptive qualitative research using observation techniques and also interviews with the principal of the research location. The results obtained explain that the school principal has not been able to carry out his role as a school principal well. The efforts made include planning, implementation and evaluation and various important roles in terms of leadership, as well as good management of teachers, students, infrastructure and other school supporters. Apart from that, the principal is also responsible for personal management, understanding the school as an organizational system, and building human resources through personal management. This research emphasizes the important role of school principals in improving the quality of education through various aspects of leadership and management.